(untitled) (Journal of Student Affairs in Africa, 2012)
The purpose of the qualitative study on which this article is based was to explore the experiences of students with visual impairments registered at an Open Distance and e-Learning University in South Africa, through a phenomenological research design. Literature was reviewed on student support in distance education and concepts from the critical disability theory, biopsychosocial model of disability, connectivism and affect theories formed the conceptual framework for the study. Telephonic semi-structured interviews were used as a technique to collect data from seven participants. Data were transcribed and then coded employing ATLAS.ti. The emerged themes centred on students’ counselling experiences, the synergy between the departments, and accessibility of services. It was also determined that students lose academic time due to the lack of resources and study materials in alternative and accessible formats. While policies and implementation plans were claimed to be in place, they do not address the reality on the ground due to a lack of coordination of disability issues, and late referral of students to counselling services. The study recommends the prioritisation of disability issues, and it needs to be incorporated in the wider university’s strategic plan to accelerate its implementation. This will translate to (i) training ICT staff on various computer software programs needed to support students with visual impairments, (ii) developing alternative formative and summative assessments, (iii) developing a graduateness and job readiness intervention programme to empower the students financially and add value to the university’s employment equity agenda, and lastly (iv) putting the disability unit at the centre of all disability matters for coordinating purposes.